Reportazh o prazdnovanii 1 maia v Moskve . Reportazh o prazdnovanii 1 maia v Moskve . Report on the Celebration of the 1st of May in Moscow . Репортаж о праздновании 1 мая в Москве - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Program devoted to the International Workers' Day (also known as May Day). Передача, посвященная Дню международной солидарности трудящихся 1 мая.